The analysis of errors of omission in english narrative composition made by EFL students - Kusumawardhani, Paramita (LPPM Universitas Mercu Buana Yogyakarta, 2017)
This research was done to investigate kinds of errors of omission, classify them, explain the characteristics of the errors and evaluate the errors produced by the English foreign learners. Errors of omission could happen because the learners were still lack of form or grammar that is supposed to have in the sentence but the learners omit it. Writing is the most difficult skill in learning English as what is spoken is different with what is written. The writing skills are complex and certainly difficult to teach, requiring not only of grammatical and theoretical devises but also conceptual and judgmental elements. The research was done by using descriptive method and the data were collected from 20 English Foreign Learners' English Narrative Composition. The results found in the learners' English narrative composition are Omission of